Penurunan Kompresi Balutan Pada Perawatan Ulkus Diabetikum Disertai Dengan Gangguan Pada Pembuluh Darah Arteri dan Vena - Nia Ratnasari; Rahma Ayu Muliawati; Farah Nibras Almira; Ida Maryati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Diabetic ulcers are one of the complications of diabetes mellitus. Diabetic ulcers can be aggravated by the presence of vascular disorders, such as arteries and veins because they will give a painful sensation to the ulcer area. Therefore, proper wound care is needed to minimize the effects of these vascular disorders, namely by reducing the compression of the wound dressing. This study aims to look at the development of diabetic ulcers accompanied by arterial and venous vascular disorders by providing decreased dressing compression during wound care. The research design used is a single case study on a patient with grade IV diabetic ulcer accompanied by arterial and venous vascular disorders. The intervention was to decrease dressing compression for 10 days of wound care.. From the wound care, improvement was obtained with reduced slough, the firm boundaries of the wound began to appear, the wound area was reduced from 10 x 7 cm to 9.3 x 7 cm. Decreasing dressing compression during wound care is considered a positive development for diabetic ulcers with arterial and venous compromise.